If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = 2x + -4x + 3 Reorder the terms: -13 = 3 + 2x + -4x Combine like terms: 2x + -4x = -2x -13 = 3 + -2x Solving -13 = 3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -13 + 2x = 3 + -2x + 2x Combine like terms: -2x + 2x = 0 -13 + 2x = 3 + 0 -13 + 2x = 3 Add '13' to each side of the equation. -13 + 13 + 2x = 3 + 13 Combine like terms: -13 + 13 = 0 0 + 2x = 3 + 13 2x = 3 + 13 Combine like terms: 3 + 13 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 5(1-4)=3(1+2) | | 5x-80=2x-11 | | y=-12x+24 | | 50x+2y=50 | | 0.16b=-12 | | -16=3x-5x-2 | | 3(2m)=x | | 20x-18=54-16x | | 3x+8y+9x+y=90 | | 8=5g-2 | | 6-5x+7x=24 | | 13x-4=2x+16 | | -17=7d-8 | | 45=198-3x | | 2x+3=-x-3 | | 9x^2+68x+159=0 | | 9+4x=36 | | 4(5-2)=48 | | 5x-59=10x+71 | | 27+2.5x=4x | | -10-4x+7x=4 | | 7C+10=28 | | x=3.25 | | 0.05-0.01(x+1)=0.01(2-x) | | 4+12=-2*6-2*4a | | -2+5x=9+3x | | T=18-20 | | T=7-2 | | -9=-24x | | 6x+99=10x-5 | | Y(2)-8y+15= | | 2x-8x-16=-6x+7-16 |